Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.mmcr.2017.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing fasciitis caused by Apophysomyces variabilis in an immunocompetent patient

Abstract: Mucormycosis caused by Apophysomyces variabilis is rarely reported in humans. A case of A. variabilis infection in an immunocompetent men after friction burns in a car accident is described. The infection presented as a rapidly progressive necrotizing infection of the skin and soft tissue, which required extensive surgical debridement and total colonic defunctioning colostomy associated with prolonged antifungal therapy. A. variabilis infection should be considered as a differential diagnosis of rapidly progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 13 publications
(23 reference statements)
2
9
0
Order By: Relevance
“…The wound progressed to cellulitis which then extended along the fascial planes to cause necrotizing fasciitis. Rodriguez et al [13] also reported similar findings in an immunocompetent male who sustained friction burns following a car accident. The infection may also be acquired in healthcare settings (healthcare-associated mucormycosis).…”
Section: Discussionsupporting
confidence: 52%
“…The wound progressed to cellulitis which then extended along the fascial planes to cause necrotizing fasciitis. Rodriguez et al [13] also reported similar findings in an immunocompetent male who sustained friction burns following a car accident. The infection may also be acquired in healthcare settings (healthcare-associated mucormycosis).…”
Section: Discussionsupporting
confidence: 52%
“…Mucormycoses are rare infections that more commonly afflict immunocompromised patients; however, recent reports demonstrate that Apophysomyces spp are an emerging pathogen in the immunocompetent host [5]. As seen in our case report, Apophysomyces varibilis has specifically been noted to mainly affect immunocompetent patients [1]. Traumatic inoculation of the organism is the most common mode of Apophysomyces infections, with almost half of all documented cases secondary to trauma.…”
Section: Discussionsupporting
confidence: 53%
“…Mucormycoses are rare infections associated with high rates of morbidity and mortality more commonly seen in immunosuppressed patients but can occur in the immunocompetent [1]. Most cases of mucormycoses are caused by the genus Rhizopus, followed by Mucor and Lichtheimia; together accounting for 70-80% of all cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Frequent agents of trauma-related mucormycosis include Apophysomes, Saksenae and licthemia [9]. Apophysomyces and Saksenae species had been reported in a number of patients with aggressive necrotising fasciitis [10,11]. An early case reports the presence of Apophysomyces in Saudi Arabia in 10-year-old girl with necrotising fasciitis following a MVA [12].…”
Section: Discussionmentioning
confidence: 99%